Description of the Use of Plasma Exchange in Dogs With Cutaneous and Renal Glomerular Vasculopathy - Skulberg, Ragnhild; Cortellini, Stefano; Chan, Daniel L.; Stanzani, Giacomo; Jepson, Rosanne E. (Frontiers in Veterinary Science, 2018)
Cutaneous and renal glomerular vasculopathy (CRGV) is a rare disease affecting dogs, with a recent apparent increase in prevalence since 2012 in the UK. This disease is characterized by a vasculopathy affecting small vessels of the kidney and skin, leading to thrombotic microangiopathy. The underlying etiology remains unknown although clinicopathological and histological findings resemble features of certain forms of thrombotic microangiopathy in people, for which plasma exchange (PEX) is considered an important component of therapy. The objective of the present study is to describe the use of PEX as adjunctive treatment in dogs diagnosed with CRGV. A retrospective review of dogs diagnosed with CRGV between 2014-2016 treated with PEX was performed. Clinical records were reviewed and data relating to signalment, diagnostic tests and management strategies were summarized. Information and complications relating to PEX were recorded. Six dogs were diagnosed with CRGV (n=2 ante-mortem, n=4 post-mortem) and underwent PEX as part of their therapy. All dogs had cutaneous lesions (n=6) and were azotemic with oliguria or anuria (n=6). All dogs underwent at least one PEX cycle; one dog had a single cycle PEX, three dogs two cycles PEX, and two dogs had one cycle PEX and one cycle of prolonged intermittent renal replacement treatment. (PIRRT). Complications seen during PEX therapy included hypothermia (n=4), tachycardia (n=2), hypotension (n=2) and hypocalcemia (n=6). Two dogs survived to discharge, the remaining four dogs were euthanized. The positive outcome in two dogs treated with PEX despite the reported high mortality rate once acute kidney injury with oliguria/anuria occurs does not confirm success of this treatment. However, survival in two dogs that were initially oligoanuric highlights that further consideration and evaluation of PEX for this patient group is warranted for this specific disease. Additional studies are urgently needed to identify the underlying etiology of CRGV before more targeted therapies can be developed. Based on our findings, further evaluation of the role of PEX in this specific disease are warranted.